COVID-19 in patients with metabolic disorders: focus on management - Antonyuk , Olena; Boiko , Nataliia (The Ukrainian Scientific Medical Youth Journal, 2023)
obesity, diabetes mellitus, cardiovascular pathologies, male gender and old age contribute to a significant worsening of the COVID-19 course and were associated with an increased risk of acute kidney injury. The study aims to define the main streams of improvement of health care of COVID-19 in patients with metabolic disorders, focusing on the risk factors, and analysing doctoral attitudes to the problems of obesity with an accent on health promotion. Research methods: systemic approach, medical-statistical, questioning, structural-logical analysis, clinical, laboratory and instrumental methods. We conducted a retrospective analysis of the medical documents of COVID-19 in-patients treated at the National Military Medical Clinical Centre “Main Military Clinical Hospital” (n=146). There were 2 groups according to the severity of COVID-19 (severe course, n= 37, non-severe – n=109). We also proposed to participate in questioning a group of doctors who were involved in the treatment of patients with COVID-19. Results. A high prevalence of diabetes and hyperglycemia in patients with a severe course of the coronavirus disease was revealed, which requires risk management both at the individual and population levels. According to the received results, majority of doctors concern on the problems of obesity and propose to take care on the preventive strategies to the patients with non-communicable diseases. Initial assessments of the clinical and laboratory data are extremely important as it could be necessary to achieve compensation of diabetes before onset of COVID-19. Health promotion of decreasing weight, giving up smoking, regular physical activity could be helpful in improvement of individual health. We propose identifying obesity as an important independent risk factor which helps in decision-making on hospitalisation of COVID-19 patients before severe respiratory insufficiency starts. Baseline creatinine should be analysed, as rapid increase serum creatinine could be associated with acute kidney injury and may need urgent renal replacement therapy while in the case of not enough resources could be challengeable and causing poor outcomes.